2023
DOI: 10.1021/acssynbio.3c00251
|View full text |Cite
|
Sign up to set email alerts
|

Design–Build–Test of Synthetic Promoters for Inducible Gene Regulation in Alphaproteobacteria

Abstract: Inducible gene expression is useful for biotechnological applications and for studying gene regulation and function in bacteria. Many inducible systems that perform in model organisms such as the Gammaproteobacterium Escherichia coli do not perform well in other bacteria that are of biotechnological interest. Typical problems include weak or leaky expression. Here, we describe an invention named ACIT (Alphaproteobacteria chromosomally integrating transcription-control cassette) that is carried on a suicide pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The inducible promoter is a synthetic construct consisting of the 16S gene promoter from R. sphaeroides flanked by Lac operators. This promoter, together with the lacI gene from E. coli , was previously tested in R. capsulatus ( Kretz et al, 2023 ) and found to have at least a 100-fold induction capacity in gene expression. Furthermore, to observe effects of the absence of Cas13a activity in vivo , we generated an additional R. capsulatus strain by inserting a transcription terminator between the cas13a gene and its promoter on the chromosome.…”
Section: Resultsmentioning
confidence: 99%
“…The inducible promoter is a synthetic construct consisting of the 16S gene promoter from R. sphaeroides flanked by Lac operators. This promoter, together with the lacI gene from E. coli , was previously tested in R. capsulatus ( Kretz et al, 2023 ) and found to have at least a 100-fold induction capacity in gene expression. Furthermore, to observe effects of the absence of Cas13a activity in vivo , we generated an additional R. capsulatus strain by inserting a transcription terminator between the cas13a gene and its promoter on the chromosome.…”
Section: Resultsmentioning
confidence: 99%
“…Most inducible promoters are based on the consensus sequence from E. coli σ 70 ; however, it is unknown how well these elements function in high GC-Alphaproteobacteria, such as N. aromaticivorans (63% GC) and R. sphaeroides (68% GC). For instance, the wild-type lac promoter from E. coli is reported to function poorly in R. sphaeroides (26). While no inducible promoters have been examined in N. aromaticivorans to our knowledge, promoters inducible by light, oxygen, crystal violet, and IPTG have been tested in R. sphaeroides (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the wild-type lac promoter from E. coli is reported to function poorly in R. sphaeroides (26). While no inducible promoters have been examined in N. aromaticivorans to our knowledge, promoters inducible by light, oxygen, crystal violet, and IPTG have been tested in R. sphaeroides (26)(27)(28)(29). Although these foreign promoters can respond to an array of possible inducers, some inducers inhibit R. sphaeroides growth (crystal violet) (26) or substantially alter physiological processes of interest (light, oxygen).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations